Решите уравнение, используя умножение на сопряженное выражение:


Решите уравнение, используя умножение на сопряженное выражение:

Xcalibur Xcalibur    1   25.04.2021 21:23    0

Ответы
ikonnikoval ikonnikoval  25.04.2021 22:00

ответ: х=4;

2x {}^{2} + 5 + 2 \sqrt{(2x {}^{2} + 5) {}^{2} - 9x {}^{2} } + 2x {}^{2} + 5 = 9x \\ 16x {}^{4} + 44x {}^{2} - 25x {}^{4} + 100x {}^{2} = 0 \\ x {}^{2} (x {}^{2} - 16) = 0 \\ x = 0 \\ x = - 4 \\ x = 4

При ОДЗ откидываем "0" и "-4".

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра